2021
DOI: 10.5758/vsi.210025
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Bridging Stent Grafts in Fenestrated and Branched Aortic Endografting

Abstract: Major branches of the aortic arch and visceral aorta pose a particular challenge for endovascular repair of aneurysms involving these regions. To preserve perfusion through these essential branches, fenestrated and branched endografts have been used. Current fenestrated and branched aortic endografts have evolved into modular devices in which the aortic main body provides appropriate access to the target branch vessel either through reinforced fenestrations or directional cuffs as the hinge point for bridging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
1
5
0
1
Order By: Relevance
“…Among the eligible studies were 15 patients with technical failure due to an inability to complete catheterization/stent deployment in TVs. The pooled estimates for TV patency were 97.6%, 96.7 and 94.3% at 12, 24 and 36 months, respectively, which are comparable to those reported for degenerative aneurysms [46,47]. Moreover, it has been observed that renal mating stents perform worse in comparison to those for the coeliac trunk or superior mesenteric artery, and fenestrations perform better when compared to branches in the mid-and long term [47,48].…”
Section: Discussionsupporting
confidence: 66%
“…Among the eligible studies were 15 patients with technical failure due to an inability to complete catheterization/stent deployment in TVs. The pooled estimates for TV patency were 97.6%, 96.7 and 94.3% at 12, 24 and 36 months, respectively, which are comparable to those reported for degenerative aneurysms [46,47]. Moreover, it has been observed that renal mating stents perform worse in comparison to those for the coeliac trunk or superior mesenteric artery, and fenestrations perform better when compared to branches in the mid-and long term [47,48].…”
Section: Discussionsupporting
confidence: 66%
“…As for the bridging stent, the balloon-expandable iCAST (Getinge, Wayne, NJ) was the bridging stent of choice in all cases due to its precise deployment, rigidity and ability to flare its most proximal segment inside the main aortic device to avoid endoleaks. 11,12 Close life-long follow-up with imaging is required in patients submitted to FEVAR procedures to access for adverse events, regardless if the DBS technique was applied or not. Therefore, the utilization of this technique did not increase the demand of follow-up imaging.…”
Section: Discussionmentioning
confidence: 99%
“…As for the bridging stent, the balloon-expandable iCAST (Getinge, Wayne, NJ) was the bridging stent of choice in all cases due to its precise deployment, rigidity and ability to flare its most proximal segment inside the main aortic device to avoid endoleaks. 11,12…”
Section: Discussionmentioning
confidence: 99%
“…5). La ecografía de control muestra mejoría de la velocidad En nuestro caso, al encontrarnos con una placa inestable, con alto riesgo de embolización, ubicada en el ostium del TBC, y siendo la estenosis del 90% y con diámetros diferentes entre la zona proximal y distal de la lesión, escogimos el stent recubierto con balón expandible (GORE ® VIABAHN ® VBX, Flagstaff, AZ), que está fabricado con anillos de acero inoxidable que brindan alta resistencia radial, flexibilidad, adaptabilidad y acortamiento mínimo con la posibilidad de posdilatar el diámetro nominal y adaptarlo a los diferentes diámetros arteriales a tratar [12][13][14] .…”
Section: Discussionunclassified